The Cardiac Mineralocorticoid Receptor (MR): A Therapeutic Target Against Ventricular Arrhythmias - Rossier, Michel F. (Frontiers in Endocrinology, 2021)
Mineralocorticoid antagonists have been proven to be useful in the treatment of severe heart failure and may even save lives in this context. However, the reason for the beneficial action of these drugs, as well as the physiological role played by the cardiac mineralocorticoid receptor (MR), are still poorly understood. While the proinflammatory action of aldosterone on the heart and the resulting fibrosis partially explain the improvement due to the anti-mineralocorticoid therapy, the reduction of sudden death is probably related to a lower occurrence of ventricular arrhythmias. In this review, the author explains the physiological mechanism linking the aldosterone-induced positive chronotropic response observed in vitro with isolated ventricular cardiomyocytes and the increased risk of ventricular arrhythmias reported in vivo in hyperaldosteronism. He describes the molecular steps involved from MR activation to acceleration of spontaneous myocyte contractions, including expression of a specific micro RNA (miR204), down-regulation of a silencing transcription factor (NRSF) and re-expression of a fetal gene coding a low threshold voltage-gated calcium channel (CaV3.2). Finally, he provides evidence suggesting aldosterone-independent and redox-sensitive mechanisms of MR activation in cardiac myocytes. Taken together, this information suggests that the use of anti-mineralocorticoid therapy could be beneficial for heart by preventing ventricular arrhythmias, not only in established hyperaldosteronism, but also in various pathological situations such as Cushing’s disease, oxidative stress, or even diabetes mellitus.